PENGARUH REPUTASI PERUSAHAAN, E-RECRUITMENT, DAN KOMPENSASI TERHADAP MINAT MELAMAR KERJA (STUDI KASUS GEN Z DIKOTA SEMARANG) - Kayani Jesiska; Hasan Abdul Rozak (CV. Lafadz Jaya, 2026)
This study aims to examine how company reputation, e-recruitment, and compensation influence Generation Z's interest in applying for jobs in Semarang. The approach used was quantitative with a survey method. Data were obtained through questionnaires completed by 100 respondents from Generation Z in Semarang. The analysis technique used was multiple linear regression using SPSS version 25 to test the relationship between independent and dependent variables. The results showed that company reputation and e-recruitment have a positive and significant influence on Generation Z's interest in applying for jobs, while compensation did not show a significant influence. From the analysis, company reputation is the most dominant factor. This indicates that Generation Z prioritizes company reputation in choosing a workplace, while e-recruitment plays a supporting factor that increases interest through the ease and efficiency of the online recruitment process. These findings confirm that company reputation and the ease of digital recruitment are the main factors that drive Generation Z's interest. Therefore, companies are advised to optimize e-recruitment and build a good reputation as a strategy to attract the best talent from Generation Z.